Characterization of Physical Forms of Donepezil Hydrochloride - Vrbinc, Miha (Acta chimica slovenica, 2007)
Different crystal forms and amorphous form of donepezil hydrochloride were prepared and characterized, using various analytical techniques. Hydrate form I is stable only at lower relative humidity (RH), while at higher RH it sorbesadditional water. Forms II, III and V were identified as polymorphs, whereas form III is thermodynamically stable. Form V was prepared by heating of hydrate IV at high temperature (about 150 °C). Three different forms of hydrate IV were obtained and characterized. Differential scanning calorimetry and X-ray powder diffraction are the most promising analytical methods for differentiation between crystal forms, both polymorphs and hydrates. Methods could be also used in determination of physical form of a drug, incorporated into solid dosage form. Thermal methods explain the most significant difference in dehydration of different forms IVČ transformation to pure polymorphic forms or mixture thereof. On heating of hydrates I and IV-1, two novel crystal forms were prepared and characterized, namely crystal forms VII and VIII.
Keywords: donepezil hidroklorid; hidrati; karakterizacija; polimorfija